2015
DOI: 10.1007/8904_2015_408
|View full text |Cite
|
Sign up to set email alerts
|

Networking Across Borders for Individuals with Organic Acidurias and Urea Cycle Disorders: The E-IMD Consortium

Abstract: Background: Patients with organic acidurias (OAD) and urea cycle disorders (UCD) are at increased risk of disability, impaired quality of life and reduced life expectancy. Clinical care in any one centre is constrained by small patient numbers; and furthermore diagnostic and treatment strategies vary between metabolic centres and countries, resulting in significant inequalities and disparity in patient outcome. Aims/methods:The overall objective of the EU-funded activity 'European registry and network for into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…Since newborn screening programmes for OAD and UCD have so far been established in a few European countries Loeber et al 2012) and symptomatic patients might be missed for various reasons, it is quite likely that the E-IMD dataset is skewed and under-represents patients with a severe phenotype to some extent. In line with this, we previously demonstrated that estimated minimum prevalences for OAD and UCD varied in different countries (Kölker et al 2015). Furthermore, the geographic distribution of rare diseases is variable and relies on genetic differences in populations such as localized founder effects.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Since newborn screening programmes for OAD and UCD have so far been established in a few European countries Loeber et al 2012) and symptomatic patients might be missed for various reasons, it is quite likely that the E-IMD dataset is skewed and under-represents patients with a severe phenotype to some extent. In line with this, we previously demonstrated that estimated minimum prevalences for OAD and UCD varied in different countries (Kölker et al 2015). Furthermore, the geographic distribution of rare diseases is variable and relies on genetic differences in populations such as localized founder effects.…”
Section: Discussionmentioning
confidence: 53%
“…It has been realized without industrial sponsoring. A detailed description of E-IMD will be published separately (Kölker et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Large observational natural history studies of UCDs in North America [Urea Cycle Disorders Consortium (UCDC; https://www.rarediseasesnetwork.org/cms/ucdc)] and Europe [European registry and network for intoxication type metabolic disease (E‐IMD; https://www.eimd-registry.org/)] have identified clinical variables, such as early disease onset, or biochemical variables, such as high initial peak plasma ammonium concentration (NH 4 + max ), to be correlated with poor long‐term outcome . However, phenotypic severity has not been predictable early during the disease course so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still uncertainty about the benefit of NBS for individuals with ASS1-D and ASL-D, diseases that are rarely included in NBS disease panels in Europe but more commonly in the United States. [14][15][16] Although recent studies from both consortia have significantly improved our understanding of the natural history of UCDs, the impact of early diagnosis (by NBS) and long-term scavenger treatment on the overall neurocognitive outcome is still unclear. 11 Previous studies have highlighted that disease onset (EO vs LO), initial peak plasma ammonium concentration (NH 4 + max ), duration of hyperammonemic episodes, and hyperammonemic encephalopathy with coma are among the best predictors of mortality and severity of the neurological impairment.…”
mentioning
confidence: 99%
“…[2][3][4]12,13 Large international registry studies from North America (the Urea Cycle Disorders Consortium [UCDC], https:// www.rarediseasesnetwork.org/cms/ucdc, activated in February 2006) and from Europe (the European Registry and Network for Intoxication Type Metabolic Diseases [E-IMD], https:// www.eimd-registry.org/, activated in January 2011) have been systematically collecting comprehensive longitudinal clinical, neurological, biochemical, and therapy-related data. [14][15][16] Although recent studies from both consortia have significantly improved our understanding of the natural history of UCDs, the impact of early diagnosis (by NBS) and long-term scavenger treatment on the overall neurocognitive outcome is still unclear. 13 Therefore, we compared and combined data from the UCDC and E-IMD registries to increase statistical power and investigated the largest cohort worldwide consisting of 1,095 individuals with UCDs.…”
mentioning
confidence: 99%